Antibaterial activity of the extracts of pineapple and pomelo against five different pathogenic bacterial isolates - Nahid Hasan, ATM; Saha, Trisha; Ahmed, Tasnia (Stamford Journal of Microbiology, 2021)
To combat the infections caused by antibiotic resistant bacteria, natural candidates are being studied to find out antibacterial activity against the drug-resistant microorganisms. Among the variety of natural candidates of plant origin, many fruits have been proved to have potent antibacterial activity. In the current study, we chose pineapple (Ananas comosus), and pomelo (Citrus maxima) to determine their efficacy against some clinical isolates. Fruit samples were subjected to prepare crude, ethanol, methanol and aqueous extract to determine their antibacterial potency. Clinical isolates were used to determine the antibacterial activity of the extracts against them. The isolates were found to be multi-drug resistant. Out of twenty-eight antibiotics, Pseudomonas aeruginosa was resistant to ten antibiotics and Salmonella spp. was resistant to nine antibiotics. Rather than the crude extracts of the fruits, ethanol and methanol extracts showed antibacterial activity towards multi-drug resistant pathogenic bacteria. Aqueous extract did not show any significant antibacterial activity at all. Extracts of pomelo fruit exhibited the highest results whereas pomelo skin and pineapple peel crude extracts were the least effective compared to the other extracts. Ethanol extract of pineapple fruit (against all isolates but Staphylococcus aureus) and methanol extract of pomelo fruit (against all isolates) showed the lowest MIC (minimum inhibitory concentration) of 187.5 μg/ml. MBC (minimum bactericidal concentration) was found (within the range of 500 μg/ml to 1000 μg/ml) only with ethanol and methanol extracts of pomelo and pineapple. As the clinical isolates were found to be inhibited by the extracts, they can be used as an alternative for treating infections caused by these bacteria. Stamford Journal of Microbiology, Vol.11 (1) 2021: 1-6